Diseño del sistema eléctrico, análisis de cortocircuito y estudio de arco eléctrico para nueva planta de MATRA - Bermúdez-Chacón, Gabriel (Instituto Tecnológico de Costa Rica, 2017)
In this document it is shown the steps taken to make the electrical design of the new productive plant of MATRA, located in El Coyol, Alajuela, taking into consideration not only the office electrical load, but also the heavy dutty production equipment. The company MATRA, with central headquarters in Santa Ana, San José, require the total design of the new productive plant to be built in El Coyol, Alajuela, this implies considering the changes of the environment, as temperature, in the equipment selection. Shortcircuit currents are going to be calculated by hand, as a demonstration, and using software ETAP this calculation is going to be proven, it is important because it helps to avoid in a failure event, material and human loses, keeping integrity of all the productive components. Complementing the short-circuit current study, arc flash study is going to be demonstrated, this phenomenon highly frequent but that not in all the cases it is done as engineering study, this to define security conditions when workers have to approach to panelboards to make maintenance routines.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Instalación eléctrica; NFPA 70; Cortocircuito; Arco eléctrico